2004
DOI: 10.1038/sj.eye.6701460
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin treatment for acute traumatic complete sixth nerve palsy

Abstract: Aims To investigate the benefits of botulinum toxin (BTX) injection for acute unilateral complete sixth nerve palsy caused by trauma. Methods We retrospectively reviewed patients treated for acute unilateral complete sixth nerve palsy caused by head injury during a 10-year period (between March 1993 and February 2003) in our hospital. The BTX treatment group was defined as patients who received BTX injection within 3 months of injury. Patients who presented within 3 months of trauma, and had no previous BTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…2 Jarrin et al 3 investigated the effect of botulinum toxin injection in 11 children with a mean age of 4.42 years and found that it was effective in decreasing the angle of deviation and even further it may provide improvement of stereoacuity with a lower number of injection compared to adults. Hung et al 4 reviewed the outcomes of patients with traumatic sixth nerve palsy who received botulinum toxin injection within 3 months of injury and suggested that botulinum toxin may be helpful in the improvement of the palsy particularly in patients with severe injury. In the present study, 4 patients had botulinum injection for the correction of abnormal head position due to Duane's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…2 Jarrin et al 3 investigated the effect of botulinum toxin injection in 11 children with a mean age of 4.42 years and found that it was effective in decreasing the angle of deviation and even further it may provide improvement of stereoacuity with a lower number of injection compared to adults. Hung et al 4 reviewed the outcomes of patients with traumatic sixth nerve palsy who received botulinum toxin injection within 3 months of injury and suggested that botulinum toxin may be helpful in the improvement of the palsy particularly in patients with severe injury. In the present study, 4 patients had botulinum injection for the correction of abnormal head position due to Duane's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the use of botulinum toxin type A is efficient in the identification of adult patients with constant strabismus who are at high risk o developing intractable diplopia after surgery [15]. The majority of studies identify the Botulinum toxin A injection into extra-ocular muscles the ideal therapy for the treatment of sixth cranial nerve palsy [1], on 36.8% of the patients with a final ocular alignment within 10 prism dioptres of orthotropia and achieved fusion and primary gaze position. There was no correlation among the number of injection for patient (the mean number of injection is 1 to 5), the size of strabismus, the grade of lateral rectus muscle function, the age, the gender or the time paresis it occurred [1].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies identify the Botulinum toxin A injection into extra-ocular muscles the ideal therapy for the treatment of sixth cranial nerve palsy [1], on 36.8% of the patients with a final ocular alignment within 10 prism dioptres of orthotropia and achieved fusion and primary gaze position. There was no correlation among the number of injection for patient (the mean number of injection is 1 to 5), the size of strabismus, the grade of lateral rectus muscle function, the age, the gender or the time paresis it occurred [1]. In our study all patients had to undergo a single injection and only in 32% of cases (9 patients) a gradual physiological recovery of the lateral rectus muscle was obtained at 6 months like if the surgical treatment could be avoided and nobody of them was candidate for a second injection; patients under-corrected at six months from the onset were been treated with surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 The severity and the laterality are also important factors affecting final prognosis. 4 Patients with bilateral and complete palsies have less chance for recovery than those with paresis, which explains partial deficits. The neuromuscular sequelae of complete unrecovered or persistent sixth nerve palsies developed contracture on the unopposed medial rectus muscle in a few months, which causes esodeviation and compensatory head position in some cases.…”
Section: Introductionmentioning
confidence: 99%